Síntese regiosseletiva de 4-trifluormetil-2-(metiltio)-3,4-diidropirimidin-4-óis 3,6-dissubstituídos com efeito inibitório enzimático - Silva, Andreia Medianeira Pedrolo Weber da (2012)
This work reports a simple and versatile new strategy for the regiosselective synthesis of N3-substituted 6-alkyl(aryl or heteroaryl)-4-trifluoromethyl-2-(methylthio)-3,4-dihydropyrimidin-4-ols, which enabled to establish the regiochemistry of the cyclocondensation reaction between trifluoromethylated enones and N-substituted 2-methylisothioureas. The N3-substituted 6-alkyl(aryl or heteroaryl)-4-trifluoromethyl-2-(methylthio)-3,4-dihydropyrimidin-4-ols were obtained from the cyclocondensation reaction of 4-alkoxy-1,1,1-trifluoromethyl-3-alken-2-ones (enones) of general formula CF3C(O)CHCR(OCH3), where R = Me, Et, Pr, C6H5, 4-MeC6H4, 4-OMeC6H4, 4-FC6H4, 4-BrC6H4 and fur-2-yl, with different N-substituted 2-methylisothiourea sulfates of general formula [R1NHC(SCH3)NH]2.H2SO4, where R1 = Me, Et, Allyl and C6H5 in basic medium. The methodology used provided the synthesis of 18 novel dihydropyrimidinols in excellent yields (85-98%) and with high regioselectivity, because only the N3-substituted compounds were obtained. The inhibitory effect of the obtained products on the activity of the enzymes acetylcholinesterase, NTPDase and 5 -nucleotidase were evaluated, showing promising results, mainly for acetylcholinesterase. For this last study was carried out molecular modeling compound that showed a higher inhibitory effect on AChE.